The making of an international investment facilitation framework : legal, political and economics perspectives / edited by Axel Berger, Manjiao Chi. - Berger, Axel, 1980-; Chi, Manjiao, 1976- (Cambridge international trade and economic law., 2025)
This book comprehensively investigates the rationale and effects of the first multilateral agreement on investment facilitation for development, including the interests of key WTO members. It adopts a multidisciplinary, transregional and data-driven approach to explore the political, economic and legal aspects pertaining to the most recent WTO agreement. The book highlights how this agreement broadens the scope of the WTO to the contentious area of foreign investment and adopts the innovative facilitation approach. The book presents cutting-edge research on the (non-)adoption of investment facilitation worldwide, the economic impact of the agreement, its legal implications and the political economy explaining why the investment facilitation for development agreement came about. The book brings together leading experts from various disciplines and practices and aims at inspiring more substantive research in this new field of international economic rule-making. This title is also available as Open Access on Cambridge Core.